Transcriptomic Analysis and Functional Characterization Reveal the Duck Interferon Regulatory Factor 1 as an Important Restriction Factor in the Replication of Tembusu Virus - Xiang, Chengwei; Huang, Mei; Xiong, Ting; Rong, Fang; Li, Linyu; Liu, Ding Xiang; Chen, Rui Ai (Frontiers in Microbiology, 2020)
Since 2010, duck Tembusu virus (DTMUV) infection has caused great economic losses to the poultry industry in China. The main clinical symptoms and pathological features of DTMUV disease are decreasing egg production, ovarian inflammation and viral encephalitis. Understanding of host anti-DTMUV responses, especially the innate immunity against DTMUV infection, would be essential for the prevention and control of this viral disease. In this study, transcriptomic analysis of duck embryonic fibroblast (DEF) cells infected with DTMUV reveals that several innate immunity-related pathways, including Toll-like, NOD-like and RIG-I-like receptor signaling pathways, are activated. Further verification by RT-qPCR confirmed that RIG-I, MAD5, TLR3, TLR7, IFN-α, IFN-β, MX, PKR, MHCI, MHCII, IL-1β, IL-6, IRF1, VIPERIN, IFIT5 and CMPK2 were upregulated in cells infected with DTMUV. Through genetic manipulations, including overexpression and knockdown/out of gene expression, we demonstrated that both VIPERIN and IRF1 may play an important role in regulation of DTMUV replication. Overexpression of either one significantly reduced viral replication as characterized by reduced viral RNA copy numbers and the envelope protein expression. Consistently, down-regulation of either one resulted in the enhanced replication of DTMUV in the knockdown/out cells. In addition, we proved that IRF1 can upregulate VIPERIN gene expression during DTMUV infection and this probably through direct binding to the VIPERIN promotor.